Mainstreaming Micro-Insurance Schemes: Role of Insurance Companies in Nepal - Sharma, Pushpa Raj (Economic Literature, 2016)
Micro-insurance refers to the relatively short term insurances meant for health, accident, crop and livestock policies. The beneficiaries are the rural people who are mostly involved in agriculture which is subject to different external shocks. Along with agro insurance, the regulator is also encouraging insurance companies to insure micro enterprises such as water mills, tea shops, rickshaws and vending carts. The poor households currently need to incur huge amounts of health expenses which are over and above their current income(s) and savings and therefore, need to resort to multiple sources of financing, of which a major source is borrowing. At present, there are 25 registered insurance companies in Nepal. Of these, 8 are private commercial life insurers, 16 are private commercial non-life insurers and 1 is composite insurer. There is no scientific calculation of the crop’s yield and of livestock, which will create ambiguity in the valuation of the property being insured. Economic Literature, Vol. XI (40-46), June 2013